Jjp Valeton jr as godsdienshistorikus - Loader, James Alfred (Hervormde teologiese studies, 1985)
JJP Valeton Jnr was one of the main founders of the theological current in nineteenth century Holland called 'the ethical theology'. Some of the most prominent members of this current were, like Valeton, Old Testament specialists. One of the main characteristics of the ethicals was their distinction between scientific knowledge and the knowledge of faith. This enabled them to adopt a critical approach to the Bible while at the same time remaining active in the service of the church. In this article it is shown how Valeton applied this principle in his work on the history of Israelite religion. An attempt is made to demonstrate how his insight was more penetrating than that of even the great Abraham Kuenen.